2015
DOI: 10.4103/0972-5229.152755
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin kinetics as a prognostic marker in severe sepsis/septic shock

Abstract: Background and Aims:To evaluate the prognostic value of change (fall) in serum procalcitonin level (PCT) in critically ill adults with severe sepsis/septic shock.Methods:This was a prospective observational study in a general purpose Intensive Care Unit of a teaching Institute. PCT was measured at admission (D0) and after 72–96 h (D4) by electrochemi-luminescence immunoassay (BRAHMS PCT kit) in adults (>18 years) admitted with severe sepsis or septic shock. Change in procalcitonin values from D0 to D4 was corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In this regard, the assessment of the temporal profile of the two biomarkers concentrations in the first 72 hours after admission has been performed. This analysis showed, in agreement with data reported in the literature [ 27 , 28 ], the utility of PCT in monitoring the evolution of the clinical response to treatment, particularly for the population of patients diagnosed with severe sepsis or septic shock, which present a significantly different trend of serial concentrations when compared to the population of subjects with a diagnosis of sepsis. Copeptin showed a similar behaviour, although not reaching statistical significance a different trend is observed in the group of patients diagnosed with sepsis, suggesting a possible application of copeptin also in monitoring the clinical response to treatment in these populations.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, the assessment of the temporal profile of the two biomarkers concentrations in the first 72 hours after admission has been performed. This analysis showed, in agreement with data reported in the literature [ 27 , 28 ], the utility of PCT in monitoring the evolution of the clinical response to treatment, particularly for the population of patients diagnosed with severe sepsis or septic shock, which present a significantly different trend of serial concentrations when compared to the population of subjects with a diagnosis of sepsis. Copeptin showed a similar behaviour, although not reaching statistical significance a different trend is observed in the group of patients diagnosed with sepsis, suggesting a possible application of copeptin also in monitoring the clinical response to treatment in these populations.…”
Section: Discussionsupporting
confidence: 90%
“…The PCT is a widely investigated biomarker in sepsis because of the short time between stimulus and PCT induction and its long half-life [ 11 , 12 ]. PCT has high sensitivity and specificity to distinguish sepsis from a systemic inflammatory response syndrome of non-infectious origin, and an elevated PCT level is disclosed to associate with sepsis in hospitalized patients independently [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…When an inflammatory/infection occurs in the individuals, the PCT production process is alternatively and independently triggered by bacterial endotoxin and inflammatory cytokines and takes place in many extrathyroid organs, including liver, lung, kidney, pancreas, brain, heart, and small intestine [ 9 , 10 ]. Under the inflammatory situation, PCT tends to rise rapidly within the first 3–4 hours after the event’s onset, peaks in the 6–12 hours, following a decrease after 24 hours and normalization within five days [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Podder et al . revealed that PCT could change significantly when it was checked serially in sepsis in patients who expired [38]. Zu et al .…”
Section: Discussionmentioning
confidence: 99%